Biometric and Intelligent Decision Making Support - Kaklauskas, Arturas (Springer, 2015)
The most important elements of intelligent decision making are exhaustive data, information and knowledge collection, extraction, analytics and rational decision making, and its adaptation to the changing micro-, mezzo-, and macro-environments. However, it is becoming difficult to put into practice lately. Decision makers end up having to examine scrupulously somewhat more data, information, and knowledge in the world of today than they ever had to previously or falling into ill-defined situations, which interfere with their compiling an array of alternatives and making appropriate decisions. For example, a real estate crisis is much like a raging hurri cane, and there is no way to hide from it. Efforts of many decision makers to change the direction of the storm are futile. A top-notch decision maker will not waste time for no reason or make unnecessary moves. Such a professional will not get excited about something he/she cannot change—for example, the critical mezzo- and macro economic situations...